The impact of China's fiscal and monetary policy responses to the great recession: An analysis of firm-level Chinese data. (March 2020) - Xue, Wenjun; Yilmazkuday, Hakan; Taylor, Jason E.
Highlights: This paper investigates the effects of Chinese financial and fiscal policies in the Great Recession. The policy effects varied based on firm-level characteristics and the industry. The Chinese financial and fiscal policies were generally effective only in the two years. Abstract: This paper investigates the effects of Chinese financial and fiscal policies designed to counter the worldwide Great Recession of 2008. We examine how policies designed to increase bank credit and health (i.e., asset liquidity, capital adequacy ratio, profitability, and bad loan ratio) influenced firm-level output, employment and investment. We also explore the impact of China's expansionary fiscal policy with regard to these firm-level variables. We find that the policy effects varied based on firm-level characteristics such as size, liability ratio, profitability, ownership and the industry in which the firm operates. With respect to the dynamic effects, our results suggest that Chinese financial and fiscal policies were generally effective in the short run, but their positive impacts ceased within two years.